2005
DOI: 10.1177/1359104505056320
|View full text |Cite
|
Sign up to set email alerts
|

Eye Movement Desensitization and Reprocessing in the Treatment of Pre-adolescent Children with Post-traumatic Symptoms

Abstract: This article describes the treatment of post-traumatic stress disorder (PTSD) using eye movement desensitization and reprocessing (EMDR) with four pre-adolescent children. EMDR has been shown to bring rapid relief in adults with PTSD. Studies are beginning to show that it can also be useful in work with young children. However, the standard protocol requires some adjustment to make it suitable for use with young children. In addition, in situations where children have complex difficulties in addition to PTSD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…Ahmad et al (2007) found that 8-session EDMR for children with PTSD, many of whom had experienced maltreatment, produced markedly reduced PTSD symptoms than controls, especially for reexperiencing symptoms. These data support other preliminary work regarding EMDR for adolescents with PTSD and the treatment has been described as possibly efficacious (Silverman et al 2008;Tufnell 2005).…”
Section: Other Treatmentssupporting
confidence: 85%
“…Ahmad et al (2007) found that 8-session EDMR for children with PTSD, many of whom had experienced maltreatment, produced markedly reduced PTSD symptoms than controls, especially for reexperiencing symptoms. These data support other preliminary work regarding EMDR for adolescents with PTSD and the treatment has been described as possibly efficacious (Silverman et al 2008;Tufnell 2005).…”
Section: Other Treatmentssupporting
confidence: 85%
“…Indeed, youth have done quite well with EMDR, with rapid reduction or elimination of trauma symptoms as reported in case reports (Cocco & Sharpe, 1993;Greenwald, 1994;Pellicer, 1993;Puffer, Greenwald, & Elrod, 1998;Tufnell, 2005) and the controlled comparison studies noted previously (Chemtob, Nakashima, & Carlson, 2002;de Roos et al, 2008;Jaberghaderi et al, 2004;Wanders et al, 2008). Several EMDR studies are of particular interest for the population in this study.…”
Section: Emdr and Mastr Treatmentsmentioning
confidence: 56%
“…No studies have directly compared the efficacy of these different forms of bilateral stimulation; because the majority of articles published on EMDR involve use of bilateral EMs, they will be the focus of the current article. Although the clinical efficacy of EMDR has been demonstrated (e.g., Russell, 2006;Tufnell, 2005), there is little evidence at present that it differs in efficacy from other therapies such as cognitive behavioral therapy. However, understanding how EMs affect the brain may help shed light on EMDR's underlying neural mechanisms, which remain controversial (e.g., Perkins and Rouanzoin, 2002).…”
mentioning
confidence: 96%